IMPLEMENTASI ALGORITMA DYNAMIC PRIORITY SCHEDULING PADA SISTEM ADMINISTRASI KANTOR KELURAHAN SORKAM KANAN - Fadli Sinaga (Universitas Ma Chung, 2026)
Advances in information technology have brought significant changes to government administration, including at the Sorkam Kanan Subdistrict Office, which still uses a manual system based on Microsoft Word. Problems that have arisen include ineffective document management, suboptimal service completion times, and the risk of data inaccuracies, especially when the volume of requests increases and the level of urgency varies. This study aims to implement the Dynamic Priority Scheduling Algorithm in the sub-district administration system to improve service efficiency and quality. This algorithm enables the system to manage queues based on priority, so that more urgent services or those with the highest priority can be handled first in a structured manner. The results of the study indicate that the implementation of this algorithm can improve service time efficiency, reduce recording errors, and increase public satisfaction. Although document submissions are made digitally, applicants must still pick up the files in person at the sub-district office. However, this system makes it easier for staff to manage administrative tasks and reduces time-consuming manual workloads.